Workplace Spirituality and Organization Citizenship Behavior: The Role of Job Satisfaction: An Empirical Investigation among School Teachers. - R. Ganaga Durga Devi (Journal of Informatics Education and Research, 2024)
Spirituality has grown immensely as an intellectual topic in recent years. The present study desires to investigate the relationship between workplace spirituality and organization citizenship behavior with mediation effect of Job satisfaction. The sample of the study included 216 teachers, working in various private schools in southern part of India. The Job satisfaction also reported to partially mediated the relationship between workplace spirituality and organization citizenship behavior. The theoretical and practical implication of the study were discussed and a series of contributory managerial implication were described accordingly.